2021
DOI: 10.1111/aej.12522
|View full text |Cite
|
Sign up to set email alerts
|

Multiple dens invaginatus in Wilson’s disease: A case report

Abstract: Wilson's disease (WD) is a rare autosomal recessive genetic disease that affects copper metabolism. Anomalies can be seen in the dento-maxillofacial structures of WD patients. Dens invaginatus (DI) is an uncommon tooth anomaly, and its incidence in decidious and permanent molars is even lower. This case report primarily explored the multiple DI of a patient with WD. A 9-year-old boy was admitted to our clinic with complaints of pain and swelling in the right lower molar area. It was learnt that the patient was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…4 Multiple occurrences of dens invaginatus cases have been reported in the literature; besides that, it may be present along with other malformations containing microdontia, taurodontism, dentinogenesis imperfecta, and gemination. 5 The aetiology of dens invaginatus is not clear; Hülsmann reported many hypotheses that have been discoursed to describe the phases of coronal invagination: central failure of development of the inner enamel epithelium, malformation of the enamel, growth compulsion of the dental arch, accelerated and destructive multiplication of the inner enamel epithelium, the fusion of two tooth germs, infection, and trauma. 1 The most accepted and frequently used classification of dens invagination is the one introduced by Oehlers, who classified it in three types according to the depth of invagination.…”
Section: Introductionmentioning
confidence: 99%
“…4 Multiple occurrences of dens invaginatus cases have been reported in the literature; besides that, it may be present along with other malformations containing microdontia, taurodontism, dentinogenesis imperfecta, and gemination. 5 The aetiology of dens invaginatus is not clear; Hülsmann reported many hypotheses that have been discoursed to describe the phases of coronal invagination: central failure of development of the inner enamel epithelium, malformation of the enamel, growth compulsion of the dental arch, accelerated and destructive multiplication of the inner enamel epithelium, the fusion of two tooth germs, infection, and trauma. 1 The most accepted and frequently used classification of dens invagination is the one introduced by Oehlers, who classified it in three types according to the depth of invagination.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Memis and Bas reported that DI was detected in bilateral bimaxillary primary and permanent molars in Wilson's disease patient's case report. Recently, Memis and Bas [27] reported that DI was detected in bilateral bimaxillary primary and permanent molars in Wilson's disease patient's case report. DI can easily be overlooked because there are no significant clinical signs of malformation.…”
Section: Discussionmentioning
confidence: 97%
“…The invagination starts in the crown and may extend into the root. The first report on dens invaginatus in a human tooth was first described by Socrates in 1856 [1], [2]. Different expressions have been used to refer to this condition including dens in dente, dentoid in dente, invaginated odontoma, dilated composite odontoma and tooth inclusion [3].…”
Section: Introductionmentioning
confidence: 99%